Single-cell profiling uncovers synovial fibroblast subpopulations associated with chondrocyte injury in osteoarthritis - Liu, Zezhong; Sun, Yongqi; Pan, Jiaoyi; Guo, Kechun; Tang, Zhi; Wang, Xiaofeng (Frontiers in Endocrinology, 2024)
Background: Chondrocytes and synovial cells participate in the pathogenesis of osteoarthritis (OA). Nonetheless, the interactions and correlations between OA synovial cells and chondrocytes remain unclear. This study aims to elucidate the interactions and correlations between OA synovial cells and chondrocytes, so as to deepen understanding of OA pathogenesis. Methods: Single-cell sequencing analysis was employed to analyze clusters of synovial and chondrocyte cells within the OA dataset. Through cell interaction analysis, the potential interactions between these two cell types were further explored. Differential gene expression analysis was used to examine the differences among synovial-related cell clusters. Results: The study identified specific characteristics of synovial fibroblasts through single-cell sequencing analysis. Subsequent cell interaction analysis revealed interactions and correlations between synovial fibroblast clusters and cell clusters in both damaged and non-damaged cartilages. CILP+ fibroblasts showed significant interactions with non-damaged chondrocytes, while POSTN+ fibroblasts exhibited significant interactions with damaged chondrocytes. Furthermore, differential gene expression analysis revealed that genes such as PRELP, CLU, COMP, TNFRSF12A, INHBA, CILP, and SERPINE2, were significantly upregulated in CILP+ fibroblasts. These genes are involved in promoting cell proliferation, inhibiting inflammatory pathways, and stabilizing cell structure, thereby exerting reparative and protective effects on chondrocytes. In contrast, COL6A3, COL6A1, COL1A2, COL1A1, COL3A1, TGF-β1, MMP2, AEBP1, SPARC, FNDC1, and POSTN were upregulated in POSTN+ fibroblasts. These genes may contribute to chondrocyte damage and further degeneration by promoting chondrocyte catabolism, driving inflammation, activating inflammatory pathways, and facilitating chondrocyte apoptosis and destruction. Conclusion: Our study elucidated the interactions and correlations between OA synovial cells and chondrocytes. CILP+ synovial fibroblasts may exert reparative and protective effects on chondrocytes of patients with OA by promoting cell proliferation, inhibiting inflammation, and stabilizing cellular structures, thereby potentially mitigating the progression of cartilage lesions in affected patients. In contrast, POSTN+ synovial fibroblasts may exacerbate chondrocyte deterioration in patients with OA by enhancing degradation, inflammation, and apoptosis, thereby exacerbating cartilage lesions. Investigating the underlying molecular mechanisms between OA synovial cells and chondrocytes refines the understanding of OA pathogenesis and provides valuable insights for the clinical diagnosis and treatment of OA.